The extant of familiarity in the maritime industry about the Sustainable Development Goals (SDGs) - Adham Sayed Mohamed Torky (Maritime Research and Technology)
This research study addresses seafarers' perception regarding the Sustainable Development Goals (SDGs), an important global issue. The current study aims to identify the degree of awareness, knowledge, and familiarity with these goals among marine officers. Specifically, the research focuses on exploring the potential relationship between maritime officers' experience and their knowledge of sustainable development goals in general and goals relevant to the maritime industry. The study uses a descriptive analytical approach, using questionnaires as the primary means of collecting data. The study reveals a lack of knowledge, awareness and familiarity with these goals among some, specifically with regard to the role of the International Maritime Organization and its efforts to achieve goals that are related to the field of the maritime industry. The findings support the necessity of incorporating educational programmers into universities and maritime institutions, with a particular emphasis on programmers that are connected to sustainable development objectives. By including this element, sailors can get a thorough grasp of the resources and actions required to accomplish those objectives. Enhancing one's knowledge and comprehension of agreements and regulations pertaining to sustainable development may also make it easier for people to meaningfully contribute to the cause of sustainability. The current study represents a significant advance in understanding these goals among seafarers, and it is expected that this will stimulate further inquiries in this area.   Received: 17 January 2024 Accepted: 28 March 2024 Published: 30 April 2024